2021
DOI: 10.1136/archdischild-2021-321672
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin and red blood cell reference intervals during infancy

Abstract: ObjectivesThere is a need for updated haematological reference data in infancy. This study aimed to define intervals for haemoglobin and red blood cell biomarkers based on data from a large cohort of longitudinally followed Swedish infants.DesignLongitudinal cohort study.SettingTwo Swedish study centres.ParticipantsThree community-based populations including 442 presumably healthy infants born at term and with umbilical cord clamping delayed to 30 s or more after birth.MethodsBlood samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…In a recently published reference material for ret-Hb, the 2.5th percentile was used as the lower limit, equivalent to a ret-Hb of 25 pg with 90% confidence interval of 21-25 pg. 22 In the present study, we combined biochemical data with AIMS, a validated assessment of gross motor development, commonly used in research and clinical settings. Even with our small sample size, we clearly demonstrated that a ret-Hb <28 pg was associated with suboptimal gross motor scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recently published reference material for ret-Hb, the 2.5th percentile was used as the lower limit, equivalent to a ret-Hb of 25 pg with 90% confidence interval of 21-25 pg. 22 In the present study, we combined biochemical data with AIMS, a validated assessment of gross motor development, commonly used in research and clinical settings. Even with our small sample size, we clearly demonstrated that a ret-Hb <28 pg was associated with suboptimal gross motor scores.…”
Section: Discussionmentioning
confidence: 99%
“…Different cut‐offs for ret‐Hb have been proposed but have relied on biochemical data only. In a recently published reference material for ret‐Hb, the 2.5th percentile was used as the lower limit, equivalent to a ret‐Hb of 25 pg with 90% confidence interval of 21–25 pg 22 . In the present study, we combined biochemical data with AIMS, a validated assessment of gross motor development, commonly used in research and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood anemia is a widespread health concern impacting young children [ 1 , 2 ] and the hemoglobin (Hb) reference varies according to the children’s age, especially in the infant period [ 3 ]. Several studies have established detailed age- and sex-specific reference intervals for hematologic parameters in healthy children [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) classifies anemia in children under 5 years of age as a condition where the Hb concentration is below 11 g/dL without arbitrary references [ 3 ]. Anemia or decreased Hb levels can be observed in febrile children and may indicate various underlying causes, including infectious or inflammatory conditions [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%